Genome instability: a pre-existing condition - Sedam, Hailey Nicole Conover, author; Argueso, Lucas, advisor; DeLuca, Jennifer, committee member; Nickoloff, Jac, committee member; Wiese, Claudia, committee member (Colorado State University. Libraries, 2018)
Copy number variations (CNV), or large amplifications or deletions in the genome, account for about 50% of human genetic diversity. CNVs across genomic regions essential for development and function can lead to disease. The underlying mechanisms of CNV formation are typically traced to a combination of endogenous or environmental sources of DNA damage coupled with defects in DNA repair, replication, and recombination. This dissertation describes two endogenous sources of genome instability involved in both mitotic and meiotic CNVs. Each chapter of this dissertation focuses on one endogenous contribution to genome instability, using the budding yeast Saccharomyces cerevisiae as a model system to investigate the conserved cellular processes that, when gone awry, can lead to CNVs. In the first phase of my research, I focused on the mitotic mutagenic effects of ribonucleotide incorporation into DNA. In the absence of RNase H2, RNA-DNA hybrids (R-loops) accumulate in the genome and ribonucleotides that are misincorporated into the DNA are not efficiently excised. Instead, the latter function is taken over by topoisomerase 1 which inappropriately removes ribonucleotides in a way that leads to accidental/unscheduled DNA double strand breaks (DSBs). My work showed that the accumulation of these lesions in RNase H deficient mutants was sufficient to increase the rate of genome rearrangements through both Loss of Heterozygosity (LOH) and Non Allelic Homologous Recombination (NAHR). Modulating the number of ribonucleotides incorporated into the leading DNA strand during replication through the use of DNA polymerase epsilon mutants affected the rate of LOH and NAHR. Additionally, the RNase H2-Ribonucleotide Excision Repair Deficient (RNase H2-RED) separation of function allele allowed further investigation of genomic instability when R-loops are properly processed but misincorporated ribonucleotides are not. The RNaseH2-RED study revealed that both ribonucleotide excision repair and R-loop removal contribute roughly equally to chromosomal stability under normal conditions. Together, the results of these studies indicated that the effects of ribonucleotides and R-loops on chromosomal instability may vary under different genomic contexts of variable R-loop formation and ribonucleotide density. Next, I designed, constructed, optimized and validated a new yeast assay system to study meiotic NAHR leading to de novo recurrent CNVs. The chromosomal rearrangements analyzed through this system are directly analogous to human pathogenic CNVs that are formed in germ cells through recombination between Low Copy Repeat elements (LCRs). While there are assays available to investigate factors involved in mitotic CNV formation, few assays have been developed to experimentally test factors involved in meiotic recurrent CNVs. Previous studies of human patient cohorts have shown that the size and distance between LCRs is strongly correlated with the frequency of recurrent CNV formation. We used this basic observation to validate our experimental system and ask whether it could faithfully recapitulate the phenomenon in our yeast model system. I constructed four diploid strains containing LCRs engineered to range in size from 5-35 Kb and determined the meiotic NAHR frequency in each construct. We detected a very clear linear correlation between LCR size and CNV frequency, and thus established our system as a pertinent assay for interrogation of factors involved in meiotic recurrent CNV formation. The results described within this dissertation have deepened our understanding of the endogenous causes of genome instability leading to CNVs, and provide perspective into the ability of normal cellular processes to trigger both mitotic and meiotic CNV formation. Additionally, I describe a unique method for future screens of both endogenous and exogenous stimulants of meiotic CNV.
Keywords: genome instability; copy number variation; Saccharomyces cerevisiae